COVID-19 pandemic: Mechanistic approaches and gender vulnerabilities - Luqman Khan; Nisar Ul Khaliq; Asad Ullah; Naseem Rafiq; Mujib Ullah (Elsevier, 2020)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a highly pathogenic virus that causes coronavirus-19 disease (COVID-19), a severe respiratory damaging syndrome with serious health complications worldwide. SARS-CoV-2 was unfamilar before the epidemic started in Wuhan, China, in December 2019. COVID-19 is currently a pandemic influencing several countries worldwide. One of the mysteries of the new coronavirus is that it is deadlier for men than women with the male mortality rate is twice as high as that of females.